In vitro activity of daptomycin, linezolid and rifampicin on Staphylococcus epidermidis biofilms - Leite, Bruna (2011)
Owing to their massive use, Staphylococcus epidermidis has recently developed significant resistance to several antibiotics, and became one of the leading causes of hospital-acquired infections. Current antibiotics are typically ineffective in the eradication of bacteria in biofilmassociated persistent infections. Accordingly, the paucity of effective treatment against cells in this mode of growth is a key factor that potentiates the need for new agents active in the prevention or eradication of biofilms. Daptomycin and linezolid belong to the novel antibiotic therapies that are active against gram-positive cocci. On the other hand, rifampicin has been shown to be one of the most potent, prevalent antibiotics against S. epidermidis biofilms. Therefore, the main aim of this study was to study the susceptibility of S. epidermidis biofilm cells to the two newer antimicrobial agents previously mentioned, and compare the results obtained with the antimicrobial effect of rifampicin, widely used in the prevention/treatment of indwelling medical device infections. To this end the in vitro activities of daptomycin, linezolid, and rifampicin on S. epidermidis biofilms were accessed, using these antibiotics at MIC and peak serum concentrations. The results demonstrated that at MIC concentration, rifampicin was the most effective antibiotic tested. At peak serum concentration, both strains demonstrated similar susceptibility to rifampicin and daptomycin, with colony-forming units (CFUs) reductions of approximately 3–4 log10, with a slightly lower response to linezolid, which was also more strain dependent. However, considering all the parameters studied, daptomycin was considered the most effective antibiotic tested, demonstrating an excellent in vitro activity against S. epidermidis biofilm cells. In conclusion, this antibiotic can be strongly considered as an acceptable therapeutic option for S. epidermidis biofilm-associated infections and can represent a potential alternative to rifampicin in serious infections where rifampicin resistance becomes prevalent.